2000
DOI: 10.1259/bjr.73.872.11026861
|View full text |Cite
|
Sign up to set email alerts
|

Some limitations in the practical delivery of intensity modulated radiation therapy.

Abstract: The resolution characteristics of intensity modulated beam (IMB) profiles produced by milled compensators and by multileaf collimators (MLCs) are independently investigated with respect to the primary fluence. It is shown that both methods have different characteristics in the longitudinal and lateral direction and, as a consequence, the resolutions of the longitudinal and lateral delivered IMB profiles differ. For both methods, the restrictions are identified. For compensators, the maximum slopes in the machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…In the worstcase scenario, where the field dimension perpendicular to the milling path is 25 cm, the resolution perpendicular to the milling path is 3.9 mm, less than the drill bit diameter of 6 mm. A detailed theoretical analysis on the influence of the drill size and other factors on the accuracy of compensator-generated intensity modulation was carried out by Meyer et al (2) The finite drill size is not considered in the dose optimization. However, the error in compensator-generated intensity map due to milling limitation is reflected and evaluated in the IMRT QA procedure.…”
Section: B2 Compensator Spatial Resolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the worstcase scenario, where the field dimension perpendicular to the milling path is 25 cm, the resolution perpendicular to the milling path is 3.9 mm, less than the drill bit diameter of 6 mm. A detailed theoretical analysis on the influence of the drill size and other factors on the accuracy of compensator-generated intensity modulation was carried out by Meyer et al (2) The finite drill size is not considered in the dose optimization. However, the error in compensator-generated intensity map due to milling limitation is reflected and evaluated in the IMRT QA procedure.…”
Section: B2 Compensator Spatial Resolutionmentioning
confidence: 99%
“…MLC-based IMRT techniques have shown several drawbacks in clinical application. (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) For instance, the total monitor units (MUs) required for a segmental MLC-IMRT treatment are often much higher than that of the corresponding nonintensity modulated treatment. As a result, the treatment delivery time is often considerably extended, and concerns about radiation contamination of the prolonged beam-on time are also raised.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Meyer et al [19], some limitations are reported because of a maximum slope of the machining process and the use of spherical cutter. These effects depend on the machine used.…”
Section: Compensator Set-up and Manufacturingmentioning
confidence: 99%
“…It can be used on any linear accelerator, it has improved spatial resolution, and the simultaneous beam intensity modulation avoids the potential interplay of MLC leaf motion and internal organ motion. The largest delivery limitations with MLC-IMRT occur because of the width of the leaves (perpendicular to leaf motion) (1). Reducing leaf width reduces this inaccuracy, but modulator-IMRT has the capability of spatial resolution higher than any current MLC.…”
Section: Introductionmentioning
confidence: 99%